Roles of IL-11 in the regulation of bone metabolism - Han, Yijing; Gao, Hui; Gan, Xinling; Liu, Jingying; Bao, Chuncha; He, Chengqi (Frontiers in Endocrinology, 2024)
Bone metabolism is the basis for maintaining the normal physiological state of bone, and imbalance of bone metabolism can lead to a series of metabolic bone diseases. As a member of the IL-6 family, IL-11 acts primarily through the classical signaling pathway IL-11/ Receptors, IL-11 (IL-11R) / Glycoprotein 130 (gp130). The regulatory role of IL-11 in bone metabolism has been found earlier, but mainly focuses on the effects on osteogenesis and osteoclasis. In recent years, more studies have focused on IL-11's roles and related mechanisms in different bone metabolism activities. IL-11 regulates osteoblasts, osteoclasts, BM stromal cells, adipose tissue-derived mesenchymal stem cells, and chondrocytes. It's involved in bone homeostasis, including osteogenesis, osteolysis, bone marrow (BM) hematopoiesis, BM adipogenesis, and bone metastasis. This review exams IL-11's role in pathology and bone tissue, the cytokines and pathways that regulate IL-11 expression, and the feedback regulations of these pathways.